Redefining rape: a proposal for rape law reform - Mohamad Yunus, Mohamad Ismail (LexisNexis, 2015)
In the case of Bunya Jalong2 , a 60-year-old's conviction was overturned by the Court of Appeal because the accused said that he used his finger tainted with his semen to penetrate the victim, instead of using his penis.3 Thus, his conduct does not fall within the legal definition of rape which defines rape as penetration by the accused's penis into the victim's vagina under certain non-consensual circumstances.4 The main issue of this proposal is to study whether the meaning of 'sexual intercourse' under s 375 of the Penal Code should be amended and expanded so that the scope of sexual intercourse is only confined or limited to penile penetration. The objective of this proposal is to review and reform the definition of sexual intercourse with special focus on the law of rape in Malaysia with reference to the current development and application of the legal position from various common law jurisdictions.